Head and neck Epstein‐Barr virus mucocutaneous ulcer: Case report and literature review. (26th April 2016) - Au, Joshua K.; Said, Jonathan W.; Sepahdari, Ali R.; St. John, Maie A.
Abstract : Objectives/Hypothesis: To report the clinical presentation, treatment, and management outcomes of patients with Epstein‐Barr virus‐positive mucocutaneous ulcer (EBVMCU) of the head and neck, which is a newly characterized pathologic entity with aggressive morphology but follows an indolent, self‐limiting clinical course. Study Design: Case report and literature review. Methods: A case of EBVMCU of the base of tongue is reported and a retrospective review of all cases of EBVMCU of the head and neck at a single academic institution was conducted between January 1, 1986 and April 1, 2015. The MEDLINE database was additionally queried from January 1, 1950 to April 1, 2015 for all reports of EBVMCU of the head and neck, and all pertinent clinical data were extracted. Results: The clinical presentation, treatment, and response of a patient with EBVMCU of the base of tongue are presented. Interim follow‐up of the patient has revealed a complete remission with discontinuation of immunosuppression and rituximab therapy. A review of the literature supports conservative management and reduction of immunosuppression. Overall, 96.6% of patients with follow‐up greater than 2 months achieved complete remission with conservative management. The current study is the largest series to report on the clinical presentation and treatment outcomes of EBVMCU of the head and neck. Conclusions: EBVMCU tends to follow an indolent and self‐limiting clinical course, responding to reduction of immunosuppression and conservative treatment. It is imperative for clinicians to consider EBVMCU in the differential diagnosis of mucocutaneous ulcers of the head and neck to avoid excessive treatment. Level of Evidence: Laryngoscope, 126:2500–2504, 2016